U źródeł romantycznej elegii — Elegia napisana na cmentarzu wiejskim Thomasa Graya - Śniedziewski, Piotr (Poznańskie Studia Polonistyczne. Seria Literacka, 2011)
From the beginning of his literary career, Thomas Gray consciously and consistently created a lyric with a poetic effect quite of its own in which a personal element (death of a friend) kept on vanishing, toposes and literary allusions overlapped (e.g. images of melancholy inspired by works of John Milton and Thomas Warton) and in which bitter philosophical reflection on life and death mounted in time. It is this reflection that predestined the groundbreaking character of Elegy written in a country churchyard and determined its popularity in English literature and beyond. The interpretation of space, the reflection on the subjectivity and the role of the epitaph (constituting at the same time a structural part of Elegy..., as well as the funeral genre that is thematically related to the Gray’s poem) have made it possible to show the poem written in mid-eighteenth century as a substantial reference point for Romantic authors transforming the genre.